Is Glucagon Receptor Activation the Thermogenic Solution for Treating Obesity? - Conceição-Furber, Ellen; Coskun, Tamer; Sloop, Kyle W.; Samms, Ricardo J. (Frontiers in Endocrinology, 2022)
Abstract A major challenge of obesity therapy is to sustain clinically relevant weight loss over time. Achieving this goal likely requires both reducing daily caloric intake and increasing caloric expenditure. Over the past decade, advances in pharmaceutical engineering of ligands targeting G protein-coupled receptors have led to the development of highly effective anorectic agents. These include mono-agonists of the GLP-1R and dual GIPR/GLP-1R co-agonists that have demonstrated substantial weight loss in experimental models and in humans. By contrast, currently, there are no medicines available that effectively augment metabolic rate to promote weight loss. Here, we present evidence indicating that activation of the GCGR may provide a solution to this unmet therapeutic need. In adult humans, GCGR agonism increases energy expenditure to a magnitude sufficient for inducing a negative energy balance. In preclinical studies, the glucagon-GCGR system affects key metabolically relevant organs (including the liver and white and brown adipose tissue) to boost whole-body thermogenic capacity and protect from obesity. Further, activation of the GCGR has been shown to augment both the magnitude and duration of weight loss that is achieved by either selective GLP-1R or dual GIPR/GLP-1R agonism in rodents. Based on the accumulation of such findings, we propose that the thermogenic activity of GCGR agonism will also complement other anti-obesity agents that lower body weight by suppressing appetite.